Role of Mitochondrial Nucleic Acid Sensing Pathways in Health and Patho-Physiology - Chowdhury, Arpita; Witte, Steffen; Aich, Abhishek (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria, in symbiosis with the host cell, carry out a wide variety of functions from generating energy, regulating the metabolic processes, cell death to inflammation. The most prominent function of mitochondria relies on the oxidative phosphorylation (OXPHOS) system. OXPHOS heavily influences the mitochondrial-nuclear communication through a plethora of interconnected signaling pathways. Additionally, owing to the bacterial ancestry, mitochondria also harbor a large number of Damage Associated Molecular Patterns (DAMPs). These molecules relay the information about the state of the mitochondrial health and dysfunction to the innate immune system. Consequently, depending on the intracellular or extracellular nature of detection, different inflammatory pathways are elicited. One group of DAMPs, the mitochondrial nucleic acids, hijack the antiviral DNA or RNA sensing mechanisms such as the cGAS/STING and RIG-1/MAVS pathways. A pro-inflammatory response is invoked by these signals predominantly through type I interferon (T1-IFN) cytokines. This affects a wide range of organ systems which exhibit clinical presentations of auto-immune disorders. Interestingly, tumor cells too, have devised ingenious ways to use the mitochondrial DNA mediated cGAS-STING-IRF3 response to promote neoplastic transformations and develop tumor micro-environments. Thus, mitochondrial nucleic acid-sensing pathways are fundamental in understanding the source and nature of disease initiation and development. Apart from the pathological interest, recent studies also attempt to delineate the structural considerations for the release of nucleic acids across the mitochondrial membranes. Hence, this review presents a comprehensive overview of the different aspects of mitochondrial nucleic acid-sensing. It attempts to summarize the nature of the molecular patterns involved, their release and recognition in the cytoplasm and signaling. Finally, a major emphasis is given to elaborate the resulting patho-physiologies.